2012
DOI: 10.1136/sextrans-2011-050405
|View full text |Cite
|
Sign up to set email alerts
|

Access to and use of unauthorised online HIV self-tests by internet-using French-speaking men who have sex with men

Abstract: Although readiness to admit use of unauthorised medical products may have influenced results, few MSM aware of the existence of self-tests actually declared having accessed one. Accessing the self-test was independently associated with both living one's sex-life with men in total secrecy and having had unprotected anal intercourse in the last 12 months, indicating that autonomous self-testing may reduce barriers to testing for this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 26 publications
6
37
3
Order By: Relevance
“…20 Establishing appropriate HIV testing interventions in the Chinese context may have far-reaching consequences because there are substantial portion of Chinese MSM who have never received HIV testing. Our study extends previous self-testing research 2123 by examining MSM self-testing practices in a middle income country setting. Furthermore, extensive formative work resulted in a high completion rate that improves on previous online studies.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…20 Establishing appropriate HIV testing interventions in the Chinese context may have far-reaching consequences because there are substantial portion of Chinese MSM who have never received HIV testing. Our study extends previous self-testing research 2123 by examining MSM self-testing practices in a middle income country setting. Furthermore, extensive formative work resulted in a high completion rate that improves on previous online studies.…”
Section: Discussionsupporting
confidence: 59%
“…This finding is consistent with a French study which found that recent unprotected anal intercourse with a casual partner was associated with self-testing. 23 In addition, our study found that HIV self-testers were twice as likely to have received an HIV test in the past 12 months, suggesting that self-testing may increase the frequency of HIV testing. This is consistent with Australian behavioral research demonstrating that MSM perceived self-testing would increase HIV testing frequency.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…A majority (87%) of MSM surveyed online in France were interested in self-tests, if available; interested men were more likely to have never tested or to have not tested in the past year, and to live their sex lives with men 'in absolute secrecy' [21]. The small proportion of the MSM (3.5%) in the study who had already accessed unapproved tests online had similar characteristics [22].…”
Section: Introductionmentioning
confidence: 91%
“…Greacen et al 10 report on use of unauthorised HIV tests, obtained online, among French speaking MSM using the internet. Very few reported using an online HIV test, but those who had reported high rates of unprotected anal intercourse, and were more likely to conceal homosexual behaviour.…”
mentioning
confidence: 99%